Características quantitativas da carcaça de cordeiros deslanados Morada Nova em função da relação volumoso:concentrado na dieta - Gonzaga Neto, Severino; Silva Sobrinho, Américo Garcia da [UNESP]; Zeola, Nívea Maria Brancacci Lopes [UNESP]; Marques, Carlo Aldrovandi Torreão; Silva, Aderbal Marcos de Azevedo; Pereira Filho, José Morais; Ferreira, Ângela Cristina Dias (Sociedade Brasileira de Zootecnia, 2006)
Com o objetivo de avaliar a influência da relação volumoso:concentrado sobre a composição tecidual e os rendimentos de carcaça e de cortes comerciais de cordeiros Morada Nova em confinamento, utilizaram-se 18 cordeiros com peso vivo (PV) inicial de 15 kg, distribuídos em seis grupos de três animais (um em cada dieta), de acordo com a relação volumoso(V):concentrado(C): 40:60, 55:45 e 70:30. Foram avaliados os pesos de corpo vazio (PCV), de carcaça quente (PCQ) e de carcaça fria (PCF), a partir dos quais foram calculados os rendimentos biológico (RB), de carcaça quente (RCQ) e de carcaça fria (RCF) e a perda de peso por resfriamento (PPR). A carcaça foi dividida em cinco cortes cárneos (perna, lombo, costelas, paleta e pescoço), os quais foram pesados para cálculo de seus rendimentos em relação ao peso da meia-carcaça. A perna foi dissecada em músculo, osso e gordura e os pesos desses tecidos foram expressos em peso absoluto e em porcentagem da perna. Calcularam-se as relações músculo:osso e músculo:gordura, o índice de musculosidade da perna (IMP) e a área de olho-de-lombo (AOL). O aumento de 30 para 60% de concentrado na dieta elevou os rendimentos de carcaça quente e carcaça fria, assim como o rendimento biológico. Os crescentes teores de concentrado na dieta não afetaram a porcentagem de músculo na perna, mas proporcionaram maior deposição de gordura e maior área de olho-de-lombo.

Eighteen lambs averaging initial body weight (BW) of 15 kg were allotted to six groups of three animals (one lamb per diet) and were fed diets with following forage:concentrate ratios (F:C): 1) 40F:60C; 2) 55F:45C; or 3) 70F:30C. Lambs of each group were slaughtered when the animal fed the diet with the highest concentrate level reached 25 kg of BW. Animals were slaughtered after 16 h of fasting (feed and water). After obtaining the slaughter body weight (SBW), animals were anesthetized by electric discharge and killed by bleeding of the carotid arteries and jugular veins. Blood was then collected and weigthed. Soon after evisceration, skin, head and extremities of the fore and rear members were removed. The gastrointestinal tract (GIT) was emptied, weighted and the value added to that of blood to obtain the empty body weight (EBW), which was calculated by subtracting SBW from GIT + blood weights. The carcasses were weighted and stored at 4°C within a 24-hours period. The empty body (EBW), hot carcass (HCW) and cold carcass weights (CCW) were all used to calculate the biological (BY), hot carcass (HCY) and cold carcass yields (CCY) as well as the weight loss by cooling process (CWL). The carcass was divided in five cuts (leg, loin, ribs, shoulder clod and neck) that were weighted for calculation of cut yields. The leg was dissected in muscle, bone and fat, and weights of these tissues were expressed in absolute weight and in percentage of leg weight. The muscle:bone and muscle:fat ratios, index of leg muscularity (ILM) and the loin eye area (LEA) were also calculated. Increasing dietary concentrate from 30 to 60% increased not only hot and cold carcass yields but also biological yield. The increasing levels of concentrate in the diet showed no effect on the percentage of leg muscle. However, it was observed an increase in both fat deposition and rib eye area.
Quantitative characteristics of the carcass of Morada Nova lambs fed different dietary ratios of forage and concentrate
Keywords: Carcass; cut yields; loin eye area; muscularity; Sheep; tissue composition; Área de olho de lombo; Carcaça; Composição tecidual; índice de musculosidade; Ovinos; rendimento de cortes